Clinical fnd epidemiological features of measles by adults in modern period - V. V. Basina; E. V. Esaulenko; K. E. Novak; M. A. Bichurina; L. V. Lyalina (Журнал инфектологии, 2021)
Positive results have been achieved during the implementation of the measles elimination program in the Russian Federation and in the Northwestern Federal District (NWFD). However, measles remains an urgent problem for some regions due to the peculiarities of this infection.Purpose of the work: to characterize the clinical, epidemiological and molecular genetic characteristics of measles in adults during the period of increasing incidence in St. Petersburg.Materials and methods: the incidence of measles in the Northwestern Federal District was analyzed in 2006–2020, and the data of 30 patients of S.P. Botkin clinical infectious diseases hospital over 18 years old (2018). The diagnosis of measles is confirmed by enzyme immunoassay. Molecular genetic studies (PCR, sequencing) were carried out at the National Scientific and Methodological Center for the Surveillance of Measles and Rubella of G.N. Gabrichevsky Moscow Scientific Research Institute of Epidemiology and Microbiology, biological material was used (nasopharyngeal washings, urine).Results: there was an increase in morbidity in some regions of the Northwestern Federal District in conditions of high coverage of the population with measles vaccinations. In the age structure in 2018–2019 the proportion of adults was 65%. 74% of patients were not vaccinated against measles. A moderate-severe course (100%) was noted, regardless of the genotypes of the virus. Clinical manifestations were characterized by febrile, catarrhal and exanthema syndrome. Diarrhea was found in 36,7% of patients, hepatomegaly in 43.4%, and an increase in transaminases in 87%. 66,7% of patients traveled outside St. Petersburg. The genotypes of the virus were identified: B3 Kabul and B3 Dublin of African origin, D8 Girsomnath of Indian origin.Conclusions: measles remains an urgent problem, in recent years, adults prevail among patients, both local and imported cases are recorded. The clinical course of the disease may be accompanied by intestinal complications and other symptoms that make it difficult to diagnose at the prehospital stage. The use of molecular genetic methods makes it possible to identify the pathogen, assess the identity of viral isolates, and improve the epidemiological surveillance of the infection.